Parental smoking and risk of hypospadias: An updated meta-analysis of observational studies - Ye, Zi-Han; Chen, Hong-Song; Zhang, Zhi-Cheng; Wang, Xiao; Liu, Xing; Wei, Guang-Hui (Frontiers in Pediatrics, 2023)
Background Inconsistent relationships have been shown between cigarette smoking and hypospadias in offspring. The purpose of this study was to summarize epidemiological evidence to evaluate the relationship between parental smoking and the risk of hypospadias. Methods Up until October 2022, PubMed, EMBASE, Web of Science, and the Cochrane Library were systematically searched for qualified research. The summary RRs and 95% CIs were calculated using either a fixed-effects or a random-effects model. There were subgroup analyses undertaken to identify potential sources of heterogeneity. Results 44 studies with 16,637,830 participants were included in our meta-analysis. Overall, maternal active smoking [risk ratio (RR) = 0.94; 95% confidence interval (CI): 0.90–0.99; P < 0.01] was significantly associated with the risk of hypospadias. And neither paternal smoking (RR = 1.00; 95% CI: 0.86–1.15) nor maternal passive smoking (RR = 0.91; 95% CI: 0.60–1.23) was associated with the risk of hypospadias. Conclusion Our study discovered an association between maternal active smoking and a decreased risk of hypospadias, which may be due to the effect of smoking on androgen. However, as numerous studies have proved that cigarette smoking during pregnancy increases the risk of overall birth abnormalities in offspring, quitting cigarettes before pregnancy positively influences the health of offspring and should be advocated worldwide. Systematic review registration [www.crd.york.ac.uk/prospero], identifier [CRD42022319378].